Likelihood of Resident Doctors Raising Concerns Within an Acute Mental Health Trust - Sarah O’Connor; Vicki Ibbett; Ruth Scally (BJPsych Open)
Aims: Raising concerns is a vital component of optimising patient safety and improving training experiences. However, resident doctors within an acute mental health trust have expressed difficulties in raising such concerns. A quality improvement (QI) project was initiated to improve the self-reported likelihood of resident doctors raising patient safety and training concerns. We developed a pulse survey to capture this data and identify barriers to raising concerns, to thus inform and evaluate change ideas.